The Complexity of DNA Transcends Epigenetics - Virginia L Naples; Bruce Rothschild (Rheumatica Acta: Open Access - Peertechz Publications, 2017)
Availability of new has afforded rheumatologists the opportunity to investigate molecular pathophysiology of joint disease techniques [1,2]. Attempts to relate DNA polymorphisms to disease activity or addresses one aspect susceptibility [3-5]. Mutations and epigenetics have received consideration [3,6], but there is another pertinent concept that needs a clearer defi nition when seeking to understand synovial pathophysiology and that is pleiotropy. This concept is not frequently discussed and its signifi cance and implications, rarely recognized. Epigenetics is the alteration of gene function in an organism, but not of the gene itself [7-11], (Reik, 2007). This is in contradistinction to pleiotropic effects, variable somatic changes induced by a single gene often simultaneously, but differentially affecting multiple body systems [12-14].